Carbohydrate Determinants of Chorionic Villi Glycoconjugates of Human Embryos, Lost due to Sporadic and Recurrent Miscarriages - Zastavnyy I.; Yashchenko A.; Lutsyk A. (Львівський клінічний вісник)
Introduction. The concept of “miscarriage” (MC) includes involuntary abortion in the period from conception to the 16th-26th week of pregnancy depending on the norms of medical legislation of different country. Approximately 15.0% of pregnancies are interrupted, and mostly (three quarters of cases) in the first trimester. Aim. To investigate lectin-binding carbohydrate determinants of the structural components of the chorionic villi of human embryos, dead as a result of sporadic and habitual non-pregnancy in the first trimester of pregnancy. Materials and methods. Tissue samples of chorionic villi of 8 human embryos, lost due to sporadic and recurrent miscarriages in the first trimester of pregnancy (gestational age 4-13 weeks), were subjected to lectin histochemistry investigation. Group of sporadic miscarriages included 3 specimens, recurrent miscarriages were represented by 5 chorionic villi samples; control group consisted of 5 samples obtained from human embryos after artificial abortions of physiological pregnancies at the respective gestational age. The histological material was fixed in 4,0 % neutral formalin and embedded in paraffin. For the general morphology investigation the 5-7 µm thick sections were stained with haematoxylin and eosin. Carbohydrate determinants of chorionic villi were detected by the lectin-peroxidase technique using 4 lectins, namely, PNA, WGA, GNA and PFA. Results. Microscopic evaluation of histological preparations of chorionic villi of 4-13-week human embryos, artificially or spontaneously eliminated, makes it possible to assess their viability and the ability to perform physiological functions. Lectinogistochemical studies showed a high affinity of PNA, GNA, WGA and PFA lectins with structural components of chorionic villi of 4-13-week human embryos. In the group of the usual miscarriage of pregnancy compared with the group of sporadic miscarriages and the control group of artificially eliminated embryos, the highest level of expression of lectins receptors WGA, GNA and PFA was found. Among the four lectins used, the highest affinity with the components of the villi of human chorionic embryos, especially with syncytiotrophoblast, was revealed by WGA lectin. Lectin PNA did not demonstrate diagnostic value for the detection of these pathological conditions, since its reactivity with the structural elements of the choronic villi of the control and experimental groups was identical. Conclusions. General morphology investigation revealed the alterations of shape and structure of chorionic villi after miscarriages in comparison to the control specimens. There was also detected an increased reactivity of surface and intravillous glycoconjugates with GNA and WGA lectins indicating the enhanced exposure of terminal Man and DGlcNAc / NeuNAc in chorionic villi obtained after miscarriages of both types. The redistribution of the lectin receptors was more obvious in chorionic villi after the recurrent miscarriages compared to the sporadic ones. These observations apparently encompass the alterations of placental barrier due to the increased apoptotic rate as well as certain imbalance in the processing and/or degradation of sialoglycans in chorionic villi.